2017
DOI: 10.1002/jsfa.8155
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme inhibitory and antioxidant peptides from digestion of larvae and pupae of Asian weaver ant, Oecophylla smaragdina, Fabricius

Abstract: These results indicate that proteins from larvae and pupae of weaver ants are potential sources of peptides with anti-ACE and antioxidation bioactivities. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…BLPHs‐I had lowest 50% inhibition concentration (IC 50 ) (0.76 mg/ml), indicating the higher scavenging activity ( p < .05) than that of BLPHs (IC 50 = 0.85 mg/ml), BLPHs‐II (IC 50 = 1.27 mg/ml), and BLPHs‐III (IC 50 = 1.21 mg/ml). This result is consistent with previous results (Pattarayingsakul et al, 2017) who reported that low molecular components from Asian weaver ant ( O. smaragdina ) protein hydrolysates also possessed good scavenging activity. Male silkmoth protein hydrolysate with MW <3 kDa exhibited higher DPPH scavenging activity (Liu et al, 2017).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…BLPHs‐I had lowest 50% inhibition concentration (IC 50 ) (0.76 mg/ml), indicating the higher scavenging activity ( p < .05) than that of BLPHs (IC 50 = 0.85 mg/ml), BLPHs‐II (IC 50 = 1.27 mg/ml), and BLPHs‐III (IC 50 = 1.21 mg/ml). This result is consistent with previous results (Pattarayingsakul et al, 2017) who reported that low molecular components from Asian weaver ant ( O. smaragdina ) protein hydrolysates also possessed good scavenging activity. Male silkmoth protein hydrolysate with MW <3 kDa exhibited higher DPPH scavenging activity (Liu et al, 2017).…”
Section: Resultssupporting
confidence: 93%
“…The commercial enzymes are used to promote the hydrolysis of protein improve its bioactivity by converting it into peptides while retaining its nutritive value (Moure, Domínguez, & Parajó, 2006). Numerous studies over the recent years have demonstrated the antioxidant properties of hydrolyzed proteins from multiple insects species, such as weaver ant ( Oecophylla smaragdina ) (Pattarayingsakul et al, 2017), male silkmoth (Liu, Wan, Liu, Zou, & Liao, 2017), and queen bee (Dong, Dong, Liu, Lu, & Yu, 2017). However, studies on the antioxidant activity of the BLP hydrolysates (BLPHs) are rarely reported, and few antioxidant sequences of BSF have been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…They contain more than 50% crude protein, according to a nutritional value evaluation, and contain more than 20 amino acids; various microelements; special chemicals, such as formic acid and herbaceous acetaldehyde, which are triterpenoid compounds, and several vitamins (Pattarayingsakul et al, 2017). Many pangolin genes are likely to be involved in the digestion of these materials because 27 of the transcripts related to the terpenoid backbone biosynthesis, and this might be one of the biological basis for their adaptions to myrmecophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The protein solution was centrifuged at 3000 g for 10 min at 4°C to collect soluble proteins in supernatant, and non-soluble materials were discarded. The digestion of proteins using pepsin (≥250 units mg −1 ) and trypsin (1000-2000 BAEE units mg −1 ) was performed as described in Pattarayingsakul et al (2017). Briefly, protein solution was adjusted to pH 2 using 6 M HCl and was digested using pepsin (0.4% w/v), at 37°C for 2 h. The pH of protein hydrolysates was then adjusted to 7.5 using 1 M NaHCO 3 and further digested at 37°C for another 2 h using trypsin (0.4% w/v).…”
Section: Preparation Of Protein Hydrolysates and Protein Fractionationmentioning
confidence: 99%